1996
DOI: 10.1300/j069v15n01_02
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Medical Presentation and Detection of Patients with a History of Alcohol Abuse or Dependence

Abstract: Women and men with alcohol use disorders differ in many respects. A retrospective medical record review of 132 patients was performed to determine outpatient clinic utilization, presentation patterns and physician actions related to patient gender and lifetime DIS-status. Women, irrespective of DIS-status, utilized out-patient health care services more often than did DIS-positive or negative men. Of 16 specific alcohol-related complaints, gender differences were only detected for trauma. DIS-positive men were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Several reasons have been proposed as to why women have more severe drinking problems and poorer psychosocial functioning than do men by the time they seek treatment. One reason is that primary care physicians are less likely to question problem drinking women than men about their alcohol use, and so women's alcohol problems are not identified during visits for medical or other mental health problems (Amodei et al. 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Several reasons have been proposed as to why women have more severe drinking problems and poorer psychosocial functioning than do men by the time they seek treatment. One reason is that primary care physicians are less likely to question problem drinking women than men about their alcohol use, and so women's alcohol problems are not identified during visits for medical or other mental health problems (Amodei et al. 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Our study encountered the classic difficulty of identifying women with alcohol problems (Amodec et al, 1996). This group of consecutively recruited abusers included only seven women (10%); in the dependent group, 15 of the 82 patients were women.…”
Section: Population Studiedmentioning
confidence: 99%
“…Women are more likely than men to seek help for alcohol problems in health care settings, yet are less likely to be identified and diagnosed. 4–6 For many of these women the visit to their primary care provider may be an important opportunity for screening and potential entry into treatment. Research has shown that screening and brief interventions for AUDs in women by primary care providers are effective in reducing future alcohol consumption.…”
mentioning
confidence: 99%
“…Research has shown that screening and brief interventions for AUDs in women by primary care providers are effective in reducing future alcohol consumption. 7,8 Given the high prevalence of female patients with AUDs and the fact that currently fewer than half of such cases are properly identified, 5,9 primary care physicians (PCPs) need to take a more active role in identifying such patients.…”
mentioning
confidence: 99%